Increasing the Efficiency of Amino Acids Detection by Electrochemical Methods on Amorphous Carbon Nitride a-CNx Electrodes. (19th June 2018) - Faure, Mathilde; Billon, Florence; Le Potier, Isabelle; Haghiri-Gosnet, Anne-Marie; Tribollet, Bernard; Pailleret, Alain; Deslouis, Claude; Gamby, Jean
Abstract : Amorphous carbon nitride a -CNx thin films were elaborated on transparent and conductive glass/indium-tin oxide (ITO) wafers to improve the electroanalytical detection of transthyretin peptide (PN) and specific amino acids (AA) from its sequence which constitutes a great challenge for the diagnosis of transthyretin-related familial amyloïd polyneuropathy (ATTR). The naphthalene-2, 3-dicarboxyaldehyde (NDA) label was used for the derivatization reaction of AAs to form N-2-substituted-1-cyanobenz-[ f ]-isoindole derivatives (CBI) which are both fluorescent and electroactive. The charge transfer resistance for all CBI derivatives permits to distinguish one AA from others, while no discrimination could be obtained using cyclic voltammetry where the peak potentials oxidation are too close enough.